2008
DOI: 10.4319/lo.2008.53.6.2533
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and oxygen isotope fractionation during dissimilatory nitrate reduction by denitrifying bacteria

Abstract: We report the first measurements of coupled nitrogen (N) and oxygen (O) isotope fractionation of nitrate by laboratory cultures of denitrifying bacteria. Two seawater strains (Pseudomonas stutzeri, Ochrobactrum sp.) and three freshwater strains (Paracoccus denitrificans, Pseudomonas chlororaphis, Rhodobacter sphaeroides) were examined. Among four strains of facultative anaerobic denitrifiers, N and O isotope effects were variable, ranging from 5% to 25%, with evidence for a drop in the isotope effects as nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
454
8

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(519 citation statements)
references
References 54 publications
57
454
8
Order By: Relevance
“…This was particularly apparent for CN25 and CN75 enrichments grown at low [NH 4 þ ] (o20 mM), which exhibited a considerable lag phase before the commencement of ammonia oxidation. Variable e values have been observed in many other organisms, including denitrifiers (Granger et al, 2008), methane oxidizers (Templeton et al, 2006), sulfate reducers (Habicht et al, 2005) and nitrite oxidizers (Casciotti, 2009;Buchwald and Casciotti, 2010), and during assimilation of NH 4 þ by heterotrophic bacteria (Hoch et al, 1992) but has not previously been reported in ammonia-oxidizing organisms. We explore two hypotheses that could explain a large apparent isotope effect at the early stages of growth (Figure 6).…”
Section: Nitrogen Isotopic Fractionationmentioning
confidence: 99%
“…This was particularly apparent for CN25 and CN75 enrichments grown at low [NH 4 þ ] (o20 mM), which exhibited a considerable lag phase before the commencement of ammonia oxidation. Variable e values have been observed in many other organisms, including denitrifiers (Granger et al, 2008), methane oxidizers (Templeton et al, 2006), sulfate reducers (Habicht et al, 2005) and nitrite oxidizers (Casciotti, 2009;Buchwald and Casciotti, 2010), and during assimilation of NH 4 þ by heterotrophic bacteria (Hoch et al, 1992) but has not previously been reported in ammonia-oxidizing organisms. We explore two hypotheses that could explain a large apparent isotope effect at the early stages of growth (Figure 6).…”
Section: Nitrogen Isotopic Fractionationmentioning
confidence: 99%
“…Dissimilatory NO − 3 reduction to NO − 2 is known to produce N and O isotopic fractionation with a characteristic slope near 1 (Granger et al, 2008). Deviations from this relationship are a common feature of the limited data sets available for OMZ's and have been interpreted as evidence for co-occurrence of other N-transformation processes including NO − 2 oxidation and contributions from N 2 fixation (Casciotti and McIlvin, 2007;Sigman et al, 2005).…”
Section: An N-loss Hotspotmentioning
confidence: 99%
“…Dissimilatory NO − 3 reduction to NO − 2 is known to produce both strong N as well as O isotopic fractionation (Granger et al, 2008) (Casciotti and McIlvin, 2007; fractionation factor, ε ∼ 25 ‰). Presumably because 15 N-depleted N 2 gas is ultimately produced via preferential loss of 14 N, this process is responsible for enriching the oceanic fixed-N inventory in 15 N (δ 15 N ∼ 5 ‰ relative to atmospheric N 2 ; Sigman et al, 2009) as compared to sources (e.g.…”
Section: A Altabet Et Al: An Eddy-stimulated Hotspot For Fixed Nmentioning
confidence: 99%
“…3B) and serves as a diagnostic of denitrification (14,(20)(21)(22). This regression of δ 18 O NO3 versus δ 15 N NO3 excluded one sample (Well JD05, 12 July) that had a lighter isotopic composition and higher NO 3 − concentration than the others (Fig.…”
Section: Significancementioning
confidence: 99%
“…− is not replenished or consumed by other processes, denitrification progressively enriches both 18 O and 15 N in the residual NO 3 − , with an O:N fractionation ratio of 0.4-0.7 in the field (14,20,21) and up to 1.0 in laboratory studies (22 Table S1), including the HBEF (10,17), have revealed little if any isotopic evidence of denitrification.…”
mentioning
confidence: 99%